Desain Pengelolaan Kelas dalam Pembelajaran Akidah Akhlak - Farissa Aulia Rahman (Journal Islamic Education, 2024)
Teacher creativity in managing the class is very important because it will support the success of teachers in overcoming student learning boredom. The purpose of this study is to determine the creativity of Islamic education teachers in managing the class to overcome learning boredom, the role of Aqidah Akhlak teachers in instilling character in students. This study is a field study using qualitative methods and certain procedures, the results of the study indicate that the role of Aqidah Akhlak teachers is to instill character values in their students, the strategies carried out by teachers include advising students to arrive on time, following madrasah regulations and teacher instructions, maintaining the cleanliness of the madrasah by not littering, and keeping cell phones and valuables away from the class, and giving sanctions to students who violate.